2000
DOI: 10.1002/(sici)1097-0215(20000501)86:3<385::aid-ijc13>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study in melanoma patients of a vaccine with peptide-pulsed dendritic cells generatedin vitro from CD34+ hematopoietic progenitor cells

Abstract: Dendritic cells (DCs) are professional antigen‐presenting cells (APCs) that can be used for vaccination purposes, to induce a specific T‐cell response in vivo against melanoma‐associated antigens. We have shown that the sequential use of early‐acting hematopoietic growth factors, stem cell factor, IL‐3 and IL‐6, followed by differentiation with IL‐4 and granulocyte‐macrophage colony‐stimulating factor allows the in vitro generation of large numbers of immature DCs from CD34+ peripheral blood progenitor cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 278 publications
(31 citation statements)
references
References 23 publications
0
24
0
1
Order By: Relevance
“…In a different approach, immature DCs were generated from CD34+ hematopoietic progenitor cells through stimulation with a predefined cytokine cocktail, and matured in vitro by pulsing with a pool of peptides derived from known melanoma antigens [267]. This study reported durable immune responses and perhaps one objective clinical response.…”
Section: Introductionmentioning
confidence: 99%
“…In a different approach, immature DCs were generated from CD34+ hematopoietic progenitor cells through stimulation with a predefined cytokine cocktail, and matured in vitro by pulsing with a pool of peptides derived from known melanoma antigens [267]. This study reported durable immune responses and perhaps one objective clinical response.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these have originally been identified in melanoma, but subsequently have been found to be expressed in various other tumors like neuroblastoma (30), gastric carcinoma (31), ovarian tumors (32), and hepatocellular tumors (33). The possible value of these antigens for tumor immunological treatment is currently being investigated (13,34,35).…”
mentioning
confidence: 99%
“…In ongoing immunotherapy protocols, DC are either generated from immature circulating blood precursors or by in vitro culture of monocytes or CD34 progenitor cells. Currently the major sources of DC for immunotherapy are: (i) CD34 cells cultured in complex cytokine cocktails including SCF, IL-3, IL-6, IL-4, GM-CSF (Mackensen et al, 2000b); (ii) monocyte derived DCs cultured in IL-4, GM-CSF (+/7 further maturation stimuli) and (iii) blood derived DC obtained through a modi®ed gradient method (Burch et al, 2000).…”
Section: Sourcesmentioning
confidence: 99%
“…A trial using CD34 derived DC matured with TNF-a, injected i.v. in 14 patients with advanced melanoma showed tumor regression in two patients, DTH reactions in four patients and expansion of peptide speci®c CTL in one patient (Mackensen et al, 2000b). In multiple myeloma patients who have undergone peripheral stem cell rescue following ablative chemotherapy DCs were loaded with myeloma speci®c immunoglobulin idiotypes puri®ed from serum and injected into the patients.…”
Section: Clinical Trialsmentioning
confidence: 99%